2009
DOI: 10.1073/pnas.0905222106
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution profiling and discovery of planarian small RNAs

Abstract: Freshwater planarian flatworms possess uncanny regenerative capacities mediated by abundant and collectively totipotent adult stem cells. Key functions of these cells during regeneration and tissue homeostasis have been shown to depend on PIWI, a molecule required for Piwi-interacting RNA (piRNA) expression in planarians. Nevertheless, the full complement of piRNAs and microRNAs (miRNAs) in this organism has yet to be defined. Here we report on the large-scale cloning and sequencing of small RNAs from the plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
119
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(134 citation statements)
references
References 30 publications
(47 reference statements)
7
119
2
Order By: Relevance
“…Deep sequencing of small RNA libraries from non-irradiated and irradiated animals and neoblast cells identified several miRNAs that were irradiation-sensitive and expressed in the neoblast cell population. In planarians, let-7a miRNA expression showed a marked decrease upon irradiation (Lu et al, 2009, Friedländer et al, 2009. In contrast, let-7a expression in mammals is suppressed in mammalian embryonic stem (ES) cells and expressed upon differentiation.…”
Section: Neoblast Specific Mirnasmentioning
confidence: 99%
See 4 more Smart Citations
“…Deep sequencing of small RNA libraries from non-irradiated and irradiated animals and neoblast cells identified several miRNAs that were irradiation-sensitive and expressed in the neoblast cell population. In planarians, let-7a miRNA expression showed a marked decrease upon irradiation (Lu et al, 2009, Friedländer et al, 2009. In contrast, let-7a expression in mammals is suppressed in mammalian embryonic stem (ES) cells and expressed upon differentiation.…”
Section: Neoblast Specific Mirnasmentioning
confidence: 99%
“…Interestingly, lin-28, a suppressor of pre-let-7a processing, was expressed in mammalian ES cells, whereas in planarians lin-28 was expressed in differentiated tissues, indicating a reversal in function and expression for let-7a and lin-28 during evolution. Deep sequencing of small RNA libraries also revealed that miRNAs belonging to the major miRNA cluster mir71a/2d/13/752 were sensitive to irradiation and expressed in the neoblast population, suggesting that miRNAs belonging to the same cluster may be co-regulated (Lu et al, 2009, Friedländer et al, 2009. Nonetheless, it is important to consider the expression of individual miRNAs from the same cluster within different neoblast populations (i.e.…”
Section: Neoblast Specific Mirnasmentioning
confidence: 99%
See 3 more Smart Citations